Factors influence the severity of premenopause syndrome - Sinambela, Megawati; Hariati, Hariati; Susanti, Dewi; Sirait, Reni Aprinawaty (Universitas Muhammadiyah Purwokerto, 2024)
Background: Premenopause syndrome triggers more severe physical and psychological problems and the emergence of various diseases. The limited research on the factors causing the severity of Premenopause syndrome has resulted in a lack of efforts to address the causative factors. Purpose: This study aims to explore factors that influence the severity of premenopause syndrome.Method: This is an analytic observational study with a cross-sectional design. Eighty-eight women aged 40-45 years were included in this study. The knowledge, attitude, age of menarche, use of hormonal contraceptives, and symptoms of premenopause syndrome observed in this study—data analysis using chi-square and multiple logistic regression.Results: Factors that influence the severity of premenopause syndrome are knowledge, attitude, age of menarche, and use of hormonal contraceptives (p<0.001). Knowledge is the most dominant factor (Exp(B) = 25.983; p<0.05)Conclusion: These results underscore the importance of increasing the knowledge of premenopause women to reduce the severity.